2019
DOI: 10.1002/cam4.2364
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic combination chemotherapy using everolimus and etoposide for the treatment of non‐Hodgkin lymphoma

Abstract: Patients with Non‐Hodgkin lymphoma (NHL) treated by conventional chemotherapeutic drugs usually require a long recovery period. However, metronomic combination chemotherapy (MCC) enhances therapeutic efficacy and decreases side effects in the treatment of NHL. In this study, we tested and compared the effects of metronomic chemotherapy (MC) using podophyllotoxin derivative etoposide (VP‐16) alone and that of MCC using both VP‐16 and everolimus (RAD001) in the treatment of NHL. Two types of NHL cells, OCI‐LY‐10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In all patients, toxicity level is of concern and the use of intermittent MC schedules might decrease toxicity while maintaining effectivity 50 . Some clinical results 53 55 have also reported a successful combination of MC and other treatment approaches.…”
Section: Discussionmentioning
confidence: 98%
“…In all patients, toxicity level is of concern and the use of intermittent MC schedules might decrease toxicity while maintaining effectivity 50 . Some clinical results 53 55 have also reported a successful combination of MC and other treatment approaches.…”
Section: Discussionmentioning
confidence: 98%
“…Chemotherapy drugs can significantly increase the autophagic activity of BCL cells (43). Multiple studies have demonstrated that inhibition of autophagy enhances chemotherapy-induced BCL cell death (44)(45)(46). However, the specific molecular regulatory effects of S100A8 on autophagy and chemoresistance in BCL cells remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study revealed that metronomic temozolomide caused the accumulation of cytotoxicity through apoptosis, cellular senescence, and DNA damage to inhibit glioblastoma cells 70 . In addition to its effect on apoptosis, MCT also exerts its antitumour effects through autophagy 71 . The metronomic use of the podophyllotoxin derivative etoposide induced autophagy in non-Hodgkin's lymphoma through increased expression of Atg5, Beclin1, and LC3 71 .…”
Section: Mechanisms and Rationale Of Mctmentioning
confidence: 99%